2020
DOI: 10.1556/030.2020.01081
|View full text |Cite
|
Sign up to set email alerts
|

Nasal colonization with methicillin-resistant Staphylococcus aureus at admission among high-risk Turkish and international patients

Abstract: Objective The aim of this study was to detect the frequency of methicillin-resistant Staphylococcus aureus (MRSA) colonization at admission in a group of presumably high-risk international or Turkish patients referred to our center for elective operations, some of whom were from countries with an unknown prevalence of MRSA infection or colonization. Methods The results of nasal swab screening for MRSA colonization performed using a specific algorithm between 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
0
1
Order By: Relevance
“…It needs to be noted, however, that the performance of the MNS (i.e., high NPV) in predicting clinical MRSA infection is intimately related to a low prevalence of MRSA infection in the community [ 10 ]. While it has been shown that a large proportion of children are intermittently colonized with S. aureus , our study, like others, has found only a minority (7.4%) of children being colonized with MRSA [ 11 , 12 , 13 ]. Moreover, of the children in this study with documented growth of S. aureus in clinical culture, MSSA dominated over MRSA (MSSA, 23/30 (76.7%) vs. MRSA, 7/30 (23.3%)), as has also been shown in a recent study of children with invasive S. aureus infections in which MRSA accounted for only one in five of the infections [ 14 ].…”
Section: Discussioncontrasting
confidence: 60%
“…It needs to be noted, however, that the performance of the MNS (i.e., high NPV) in predicting clinical MRSA infection is intimately related to a low prevalence of MRSA infection in the community [ 10 ]. While it has been shown that a large proportion of children are intermittently colonized with S. aureus , our study, like others, has found only a minority (7.4%) of children being colonized with MRSA [ 11 , 12 , 13 ]. Moreover, of the children in this study with documented growth of S. aureus in clinical culture, MSSA dominated over MRSA (MSSA, 23/30 (76.7%) vs. MRSA, 7/30 (23.3%)), as has also been shown in a recent study of children with invasive S. aureus infections in which MRSA accounted for only one in five of the infections [ 14 ].…”
Section: Discussioncontrasting
confidence: 60%